Size-dependent radiative cooling power of glass-polymer metafilms - Wenhui Xie; Zhenyu Fan; Gang Tan; Ronggui Yang; Yujie Wei (Materials & Design)
Glass-polymer metamaterial, in which glass microspheres are randomly distributed in a polymer matrix, has been demonstrated to be a highly efficient daytime radiative cooling material that can be manufactured via roll-to-roll processes at scale and at low cost. In this work, we conducted a comprehensive study on the effect of size on the radiative cooling power of this hybrid metamaterial, examining the influence of microsphere size, film thickness, and microsphere volume fraction. Our results reveal that the net radiative cooling power increases rapidly with both the microsphere volume fraction and film thickness, although the rate of increase gradually diminishes. In particular, the glass-polymer hybrid metamaterial film, with a thickness as low as 50 μm and containing approximately 8 % SiO2 microspheres, exhibits uniform and strong emission across the entire atmospheric window. Regarding the effect of microsphere size, the net radiative cooling power initially increases, then slightly decreases before finally reaching a steady plateau. Depending on the microsphere volume fraction and film thickness, the optimal microsphere radius ranges from 1.4 to 4.0 μm. This study provides guidance for numerical calculations in designing similar thermal-control metamaterials.